Green Human Resource Management, Green Work Engagement, and Ethical Leadership - Rahardyani Sekar Negari; Salamah Wahyuni (Danadyaksa: Post Modern Economy Journal, 2026)
This study focuses on batik SMEs in Surakarta, particularly in Laweyan and Kauman, which have adopted sustainable production practices using natural dyes and environmentally friendly materials (Wasita, 2025). However, it remains unclear whether these sustainability values have been fully reflected in employees’ green behavior, even though the success of sustainability policies depends on how well individuals internalize and apply such values in their daily work activities. This study aims to analyze the influence how Green Human Resource Management, Green Work Engagement, and Ethical Leadership can encourage the consistent emergence of Green Behavior among SME actors, in order to bridge the gap between awareness and concrete actions in supporting sustainability. Data collection in this study was conducted through questionnaires, which are instruments consisting of a systematically and clearly designed list of written questions prepared by the researcher to be answered by the respondents. The results revealed that all the hypothesis testing in the research model, when Batik SMEs seek to improve their employees’ green behavior whether formal (in-role), voluntary (extra-role), or innovative (green innovative work behavior) this can be achieved by strengthening ethical leadership, optimizing Green Human Resource Management (GHRM) practices, and enhancing employees’ green work engagement. These findings are demonstrated by the fact that Ethical Leadership, Green Human Resource Management, and Green Work Engagement predominantly have positive and significant effects on various dimensions of employees’ green behavior within the Batik SME environment.